Application of MPI-IO in Parallel Particle Transport Monte-Carlo Simulation - Zeyao, Mo; Zhengfeng, Huang (Parallel algorithms and applications, 2004)
Parallel computers are increasingly being used to run large-scale applications that also have huge input/output (I/O) requirements. However, many applications usually obtain poor I/O performance on parallel machines. In this paper, we will address the parallel I/O of a parallel particle transport Monte-Carlo simulation code (PTMC) on a parallel computer. This paper shows that, without careful treatments, the I/O overheads will ultimately dominate the elapsed simulation time. Fortunately, we have successfully designed the parallel MPI I/O methods for it. In particular, for a benchmark application MAP6 with 105 steps of 100,000 samples, we have elevated the speedup from 10 with 64 processors to 56 with 90 processors. Moreover, our method is scalable for a larger number of CPUs and a larger number of samples.